Complete Nucleotide Sequence of pGA45, a 140,698-bp IncFIIY Plasmid Encoding blaIMI-3-Mediated Carbapenem Resistance, from River Sediment - Dang, Bingjun; Mao, Daqing; Luo, Yi (Frontiers in Microbiology, 2016)
Plasmid pGA45 was isolated from the sediment of Haihe River using E. coli CV601 (gfp-tagged) as recipients and indigenous bacteria from sediment as donors. This plasmid confers reduced susceptibility to imipenem which belongs to carbapenem group. Plasmid pGA45 was fully sequenced on an Illumina HiSeq 2000 sequencing system. The complete sequence of plasmid pGA45 was 140,698 bp in length with an average G+C content of 52.03%. Sequence analysis shows that pGA45 belongs to incFIIY group and harbors a backbone region shares high homology and gene synteny to several other incF plasmids including pNDM1_EC14653, pYDC644, pNDM-Ec1GN574, pRJF866, pKOX_NDM1 and pP10164-NDM. In addition to the backbone region, plasmid pGA45 harbors two notable features including one blaIMI-3-containing region and one type VI secretion system region. The blaIMI-3-containing region is responsible for bacteria carbapenem resistance and the type VI secretion system region is probably involved in bacteria virulence, respectively. Plasmid pGA45 represents the first complete nucleotide sequence of the blaIMI-harboring plasmid from environment sample and the sequencing of this plasmid provided insight into the architecture used for the dissemination of blaIMI carbapenemase genes.